Acciones finales discriminantes de voleibol en categorías de formacion masculina: importancia del saque en los partidos igualados - Davila-Romero, C.; Garcia-Hermoso, A. (Revista Internacional de Ciencias del Deporte, 2012)
The aim of this study was to confirm the importance of the serve on formatives stages male volleyball and determine what actions are relevant to the victory in the fifth set on equal matches. We collected a total of 218 matches (102 and 116 in infantile and cadet categories), 755 sets (354 and 401 in infantile and cadet categories) and 744 players (360 and 384 in infantile and cadet categories) of the Spain Volleyball Championships held in Huelva and Valladolid in 2008 and 2009 (Spain) at school-age (12-16 years). Finally were analyzed only the fifth set of equal matches. The results of the discriminant analysis showed how the positive serve in both categories, the error in infantile category and in cadet positive attack may predict victory and / or defeat in the fifth set. They suggest that, in both categories, the success in offensive actions and control of the technical pattern of the serve are essential in these closed matches during set decisive moments.